Effect of various nitrogen doses on chromium and nickel content, accumulation and translocation in yellow lupine - Wysokiński, Andrzej; Kuziemska, Beata (Polish Journal of Agronomy, 2020)
The aim of the study in the field experiment was to determine the effect of different nitrogen fertilization and growth phases on the nickel and chromium content, accumulation and translocation in yellow lupine. The test factors included nitrogen doses (0, 30, and 120 kg ha-1) introduced into the soil prior to seed sowing, as well as growth stages (BBCH 65 and 90) of tested plant. Mineral nitrogen was introduced to the soil as ammonium sulphate (NH4)2SO4. Plants harvested at 65 BBCH were divided into roots, steams, leaves and flowers, whereas those harvested at 90 BBCH were divided into roots, steams, leaves, pods and seeds. 30 kg N ha-1 application did not significantly impact on the content and uptake of Cr and Ni by lupine. The content of these heavy metals in lupine decreased after fertilization with120 kg N ha-1. This N dose did not significantly affected the amounts of Cr and Ni taken up by tested plants. Cr bioaccumulation coefficient did not significantly depend on N fertilization used, while the increase of N doses decreased the value of this coefficient for Ni. Under the conditions of growing lupine on soil with a natural chromium and nickel content, no tendency to hyperaccumulate these heavy metals was found.